Mitigating mango fruit decay - Darshan, Devi; Gill, K B S; Devi, Reema (Indian Horticulture, 2024)
Mango postharvest decay is a major concern for the mango growers as it is highly perishable in nature. There are several reasons that lead to postharvest decay such as harvesting of fruits at sub-optimal stages, mechanical injury, poor packaging and transport conditions, and high level of pre-harvest infection. The article highlights the main causes responsible for postharvest decay and its management strategies.